GEROJENE DALAM ADAT PERNIKAHAN SUKU KAILI DITINJAU DARI FIQHI MUNAKAHAT - Bahdar - (Paedagogia: Jurnal Pendidikan, 2019)
This study specifically examines the implementation of gerojene in the custom of Kaili tribal marriage in terms of fiqh Munakahat. The problem raised was how to understand and implement gerojene according to the Kaili tribal wedding customary law. This research is based on the views of some cultural experts that tradition can be seen as an act and behavior that prevails in a society, both in the form of habits and rules that are worked on from generation to generation inherited from ancestors since time immemorial. The definition is that if it is associated with the Kaili tribe's marriage customs, namely gerojene, then what is meant is the actions and rules held in a marriage ceremony inherited from ancestors and have been held for a long time until today are still maintained and practiced in traditional wedding ceremonies the Kaili tribe in Central Sulawesi. This research data comes from secondary data in the form of theories quoted from books, research journals, fiqh munakahat, and other writings by quoting directly or indirectly. Primary data or data collected from the field of research. Primary data collection uses two types of methods. First observation. The researcher went to the research location. The location of this study was in two districts and one city. Donggala Regency, Sigi Regency and Palu City. This observation activity is to meet traditional Kaili figures. Both methods are in-depth interviews. This was intended to find out the understanding and implementation of gerojene customs in the Kaili tribe marriage through question and answer. The answers given will clarify the problem under study. Through this research, it is known that there are differences in the understanding and procedure for the implementation of gerojene in the Kaili tribal marriages of the past with the Kaili tribe today. The words gerojene were pronounced by the customary leader as the representative of the bride of the prospective wife. After that the prospective husband answered as his agreement. The end of this pledge of women and men has legitimately become husband and wife. This event must be attended by a mother father or representing men and women and witnessing traditional and family leaders.